Nucleon flavor asymmetry in a statistical model of confined quarks - Trevisan, L. A.; Tomio, Lauro [UNESP]; Frederico, T. (AIP Publishing, 2004)
We obtain a simultanously fit to the nucleon experimental data of the flavor asymmetry d-/ū in the sea, and the ratio d/u. We use a statistical thermal model, where the quarks are confined inside the nucleon by a linear potential. We adjust the Gottfried sum rule violation with a temperature parameter. To obtain a good fit to the ratio d-/ū it was also included the contribution of gluon splitting processes.